Corrosion behavior of ferritic stainless steel alloyed with different amounts of niobium in hydrochloric acid solution - Demiroren, Hulya (Springer, 2009)
The corrosion behavior of stainless steel alloys containing corrosion-resistant elements was investigated. Ferritic stainless steel (FSSs) electrodes were synthesized by applying a scan rate of 1 mV s(-1). Stainless steels were used unalloyed and alloyed with about 0.5, 1, and 3 wt% elemental Nb. The samples were obtained from casting and forging. The samples were classified into three groups. In the first group, samples were unhomogenized and remained in production condition. In the second and third groups, samples were exposed to homogenization at 1,100 A degrees C for 30 min or 180 min, respectively, and then quenched. The corrosion performance of the FSSs was investigated in 0.3 M HCl acid solution using electrochemical impedance spectroscopy (EIS). Corrosion resistance was calculated using the Stearn-Geary equation. SEM investigations of samples immersed in 0.3 M HCl acid solution for 60 and 360 min were performed. SEM micrographs showed generalized pitting. Consequently, it was determined that niobium has a beneficial effect on the corrosion resistance of FSS since niobium reacts with carbon to form stable carbides.
Keywords: Electrochemical impedance spectroscopy; Ferritic stainless steel; Nyquist diagram; Hydrochloric acid solution